2018
DOI: 10.1111/aeq.12245
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Colonial Legacies: Voices of Indigenous Youth on Child Welfare (Dis)Placements

Abstract: In this thesis I examine how settler colonialism shapes child welfare (dis)placements. I use the term (dis)placement as a point of departure to understand the historical connection between the child welfare and residential school systems. Indigenous youth collaborators, who recently exited the child welfare system, contributed to this research through arts and storytelling. Their verbal and artistic testimonies attest to the degree that child welfare is part of larger historical and political processes includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Forty-two articles [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ], from 38 unique studies, reported on aspects of Indigenous youth wellbeing in Canada. Our thematic analysis identified eight aspects of wellbeing for this population: basic resources for survival; safety and stability; relationships with others; culture and spirituality; knowledge, opportunities, and the future; identity; resilience and independence; and recreation and interests.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty-two articles [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ], from 38 unique studies, reported on aspects of Indigenous youth wellbeing in Canada. Our thematic analysis identified eight aspects of wellbeing for this population: basic resources for survival; safety and stability; relationships with others; culture and spirituality; knowledge, opportunities, and the future; identity; resilience and independence; and recreation and interests.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of having a safe and stable living environment is essential to achieving wellbeing for Indigenous youth in Canada [ 40 , 41 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 52 , 53 , 54 , 55 , 56 , 58 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 70 ]. A number of negative incursions undermine the attainment of this safe environment: colonisation and racism [ 40 , 43 , 44 , 45 , 46 , 47 , 49 , 53 , 54 , 55 , 56 , 58 , 60 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 81 ] effects include microaggressions, marginalisation, violence, suicide and substance abuse [ 45 , 47 , 49 , 53 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tar Sands Gigaproject's oil extraction produces toxic waste that flow into water systems, resulting in rare cancers endangering many natives' lives [4]. Another contemporary example of genocidal effects owing to colonial legacy involves the "child welfare (dis)placements" of Indigenous children and youth who "die in care" through homicide, suicide, and so forth at more significant rates than their non-indigenous counterparts [9]. As typifies genocidal campaigns, Navia et al charge, the Canadian citizenry is complicit in the "ongoing forms of settler colonialism experienced in child welfare systems today" (p. 146), making that much more dangerous the racist systems ironically designed to protect and educate native children who are overrepresented in systems of care.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Histories of settler colonial intervention that systematically separate and disrupt Indigenous families and communities in these countries are well documented (Buti, 2002;Jacobs, 2006;Milloy, 2017;Simon & Smith, 2001). Structural legacies of poverty and intergenerational trauma-imposed by current and historical settler colonial policies and practices resulting in losses of land, culturally based systems of knowledge and care, and community ties-shape a context in which Indigenous children today are overrepresented in child welfare systems (Bombay et al, 2013;Brittain & Blackstock, 2015;Johnston, 1983;Milloy, 2017;Navia et al, 2018). In recent decades, a transition toward some Indigenous communities taking over jurisdiction of child welfare systems, along with some political endorsement of increased Indigenous self-determination, has accompanied shifts in both recognition of these traumatic histories and possibilities for redressing them (Libesman, 2014;MacDonald & Levasseur, 2014;Rae, 2009).…”
mentioning
confidence: 99%